(-)-Epigallocatechin-3-gallate Reduces Cigarette Smoke-Induced Airway Neutrophilic Inflammation and Mucin Hypersecretion in Rats - Liang, Yingmin; Liu, Kenneth W. K.; Yeung, Sze C.; Li, Xiang; Ip, Mary S. M.; Mak, Judith C. W. (Frontiers in Pharmacology, 2017)
Background: Cigarette smoking is the leading cause of chronic obstructive pulmonary disease (COPD). (-)-Epigallocatechin-3-gallate (EGCG), the major catechins in Chinese green tea, has been studied for its anti-oxidative and anti-inflammatory properties in cell and animal models. In this study, we aimed to analyze the effects of EGCG on cigarette smoke (CS)-induced airway inflammation and mucus secretion in the CS-exposed rat model. Methods: Male Sprague-Dawley rats were randomly divided into either sham air (SA) or CS exposure. EGCG (50 mg/kg b.wt.) was given by oral gavage every other day in both SA and CS-exposed animals. Oxidative stress and inflammatory markers were determined in serum and/or bronchoalveolar lavage fluid (BALF) by biochemical assays or ELISA. Lung morphological changes were examined by Periodic Acid-Schiff (PAS), Masson’s Trichrome staining and immunohistochemical analysis. Western blot analysis was performed to explore the effects of EGCG on epidermal growth factor receptor (EGFR)-mediated signaling pathway. Results: EGCG treatment attenuated CS-induced oxidative stress, lung cytokine-induced neutrophil chemoattractant-1 (CINC-1) release and neutrophil recruitment. CS exposure caused an increase in the number of goblet cells in line with MUC5AC upregulation, and increased lung collagen deposition, which were alleviated in the presence of EGCG. In addition, CS-induced phosphorylation of EGFR in rat lung was abrogated by EGCG treatment. Conclusions: EGCG treatment ameliorated CS-induced oxidative stress and neutrophilic inflammation, as well as airway mucus production and collagen deposition in rats. The present findings suggest that EGCG has a therapeutic effect on chronic airway inflammation and abnormal airway mucus production probably via inhibition of EGFR signaling pathway.